Ideological Criticism of Sustainable Development: Degrowth and Challenges to Ecological Capitalism - Rizky, Much Setiawan; Djunatan, Stephanus (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study aims to examine the limitations of ethical green consumption as a solution to the environmental crisis, highlighting how such practices operate within an economic system that in fact reinforces ecological degradation. Green consumption is seen as incapable of addressing the root causes of the crisis, as it remains trapped in the logic of endless growth, commodification, and the individualization of ecological responsibility. This research is crucial given the increasing popularity of ethical consumption narratives in policymaking and popular culture, despite their often illusory contributions to sustainability. The study employs a qualitative approach grounded in semiotics and interpretive analysis. Data are collected through a literature review of academic texts, policy documents, and media narratives that engage with the concepts of green consumption and degrowth. The analysis deconstructs signs, symbols, and metaphors within sustainability discourse and situates them within broader social and ideological contexts. The main finding reveals that ethical green consumption functions as an ideological mechanism that stabilizes the capitalist economic system through moral aesthetics, rather than as a transformative effort that addresses the ecological crisis at its root. The discourses of green growth and sustainable development promoted by global institutions are framed in technocratic language that conceals power relations, global inequality, and ecological imperialism. In contrast, degrowth emerges as an alternative paradigm that proposes a redefinition of prosperity based on sufficiency, redistribution, reciprocity, and global ecological justice—particularly through selective contraction in wealthy nations and development autonomy for the Global South. The study's implications point to the need for a shift in sustainability policy and culture—from an emphasis on individual responsibility toward systemic transformation and global justice. This research contributes original insights by integrating semiotic analysis and critical theory to uncover the growth ideology embedded in green consumption and by rearticulating degrowth not as austerity, but as a political, ecological, and social vision for a just and sustainable future.